In search of intimacy: forms of prayer in vernacular language in fourteenth and fifteenth-century France - Alfeu de Almeida, Leticia Goncalves [UNESP] (Programa Pos-graduacao Historia Univ Estado Do Rio De Janeiro, 2020)
This article analyzes a series of French prayer texts composed in the fourteenth and fifteenth centuries. These texts taught the lay public devotional modalities considered internal, that is, inspired by monastic practices based on reading, meditation and private prayer. It is worth exploring how such texts, which were written by clergymen and differed from the Books of Hours - which in that period still privileged Latin - presented a program of virtuous life for lay people interested in more fully dedicating themselves to prayer in their daily life. It is important to consider the value of such teachings in the context of tensions generated by the papal schism - which divided the Church between Rome and Avinhao from 1378 to 1417 - and the clerical reprobation of devotional excesses coming from those who were then seeking more intimate and direct ways of talking with God, such as visions, ecstasies and stigmata, and the disregard of sacraments.
Keywords: prayer; lay devotion; Medieval France; vernacular language; intimacy